2022
DOI: 10.3390/ma15207388
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical and Experimental Study on Cutting Characteristics and Transient Cutting Force Modeling in Feed Directional Ultrasonic Vibration-Assisted Cutting of High Strength Alloys

Abstract: Ultrasonic vibration-assisted cutting (UVC) is progressively being used in machining as it can significantly promote the fabrication process. However, the ultrasonic vibration affecting the cutting process is still controversial. The full-transient cutting process is proposed in this study to analyze the affecting mechanism induced by ultrasonic vibration in the cutting process. This novel model is the first developed based on the fact that ultrasonic vibration would change mechanical behaviors and the cutting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Sun and colleagues proposed an analytical model for calculating the specific cutting energy for high-precision diamond tool machining of titanium alloys, in particular, Ti6Al4V alloy [96]. Chen et al studied ultrasonic vibration machining (UVC) and its effect on the cutting process [97]. They found a significant increase in the shear angle and decrease in the shear stress in the primary cutting zone by introducing ultrasonic vibrations into the cutting zones.…”
Section: Cutting Force Calculation Using Analytical Modelsmentioning
confidence: 99%
“…Sun and colleagues proposed an analytical model for calculating the specific cutting energy for high-precision diamond tool machining of titanium alloys, in particular, Ti6Al4V alloy [96]. Chen et al studied ultrasonic vibration machining (UVC) and its effect on the cutting process [97]. They found a significant increase in the shear angle and decrease in the shear stress in the primary cutting zone by introducing ultrasonic vibrations into the cutting zones.…”
Section: Cutting Force Calculation Using Analytical Modelsmentioning
confidence: 99%
“…Among the cutting parameters, the cutting depth has the greatest influence on the cutting force, followed by the cutting speed and feed rate. Chen et al [13] systematically studied the influence of UAT on cutting performance in different scenarios, and proposed a new model to determine the average cutting force and transient cutting force. Maurotto et al [14] compared the surface texture of UAT and CT titanium alloy and observed that the surface of CT has obvious periodicity compared with UAT.…”
Section: Introductionmentioning
confidence: 99%